2021
DOI: 10.1177/19714009211026923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dural venous sinus stenting in treating idiopathic intracranial hypertension with acute vision loss

Abstract: Introduction Dural venous sinus stenting (VSS) is an effective, durable treatment for patients with idiopathic intracranial hypertension (IIH) due to underlying venous sinus stenosis. However, the use of venous sinus stenting to treat IIH with acute vision loss has rarely been described. Methods A retrospective chart analysis identified patients who received VSS for fulminant IIH, defined as acute (< 8 weeks) visual field loss to within the central 5° and/or a decrease in visual acuity to less than or equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…In addition, in looking only at the 3month post-VSS visit, it is possible that some patients had further improvement in pulsatile tinnitus later. Compared to prior studies reporting successful weaning of most of their patients off medication after stenting (16,27), there were 58 (67.4%) patients in our cohort still requiring IIH management medication post-stenting. This, too, is likely due to the short follow-up period used for our analyses (4.0 months in our cohort versus 15.12 and 19.70 months in the Touzéand Zehri studies).…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, in looking only at the 3month post-VSS visit, it is possible that some patients had further improvement in pulsatile tinnitus later. Compared to prior studies reporting successful weaning of most of their patients off medication after stenting (16,27), there were 58 (67.4%) patients in our cohort still requiring IIH management medication post-stenting. This, too, is likely due to the short follow-up period used for our analyses (4.0 months in our cohort versus 15.12 and 19.70 months in the Touzéand Zehri studies).…”
Section: Discussioncontrasting
confidence: 79%
“…Even this practice might change; there are now credible reports of satisfactory visual outcomes from TSS stenting as first treatment even for fulminant IIH. 59,60 In our view PTC patients with significant visual impairment need to be assessed, expeditiously, by a multi-disciplinary team in a tertiary facility that offers all possible interventional treatments for PTC: ONSF, TSS, temporary lumbar CSF drainage, 46 and occasionally, CSF shunting. 22,61 As in all retrospective case series of uncommon disorders, there are limitations due to selection bias, small numbers of patients and missing or limited data.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years of this study, in contrast to the first 5 years, we have tended to offer ONSF only to patients with acute or fulminant PTC as an emergency, sight‐saving measure. Even this practice might change; there are now credible reports of satisfactory visual outcomes from TSS stenting as first treatment even for fulminant IIH 59,60 . In our view PTC patients with significant visual impairment need to be assessed, expeditiously, by a multi‐disciplinary team in a tertiary facility that offers all possible interventional treatments for PTC: ONSF, TSS, temporary lumbar CSF drainage, 46 and occasionally, CSF shunting 22,61 …”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies have shown promising results with venous stenting, with improvements in symptoms and visual function and significantly reduced intracranial pressure. 18,20,27,31,56 Compared with other treatment modalities, venous stenting may offer several advantages, including a lower risk of complications and a more durable solution. However, more studies are needed to compare the long-term outcomes and cost-effectiveness of venous stenting vs other treatment options for IIH.…”
Section: Discussionmentioning
confidence: 99%